SNAREs SYP121 and SYP122 Mediate the Secretion of Distinct Cargo Subsets - Waghmare, Sakharam (Plant Physiol, 2018)
SNARE (soluble N-ethylmaleimide-sensitive factor attachment protein receptor) proteins drive vesicle fusion and contribute to homoeostasis, pathogen defense, cell expansion, and growth in plants. In Arabidopsis (Arabidopsis thaliana), two homologous Qa-SNAREs, SYNTAXIN OF PLANTS121 (SYP121) and SYP122, facilitate the majority of secretory traffic to the plasma membrane, and the single mutants are indistinguishable from wild-type plants in the absence of stress, implying a redundancy in their functions. Nonetheless, several studies suggest differences among the secretory cargo of these SNAREs. To address this issue, we conducted an analysis of the proteins secreted by cultured wild-type, syp121, and syp122 mutant Arabidopsis seedlings. Here, we report that a number of cargo proteins were associated differentially with traffic mediated by SYP121 and SYP122. The data also indicated important overlaps between the SNAREs. Therefore, we conclude that the two Qa-SNAREs mediate distinct but complementary secretory pathways during vegetative plant growth.